PENGARUH FINANCIAL LEVERAGE, PROFITABILITY DAN EARNING PER SHARE TERHADAP INCOME SMOOTHING DENGAN CORPORATE GOVERNANCE SEBAGAI MODERASI PADA PERUSAHAAN PERBANKAN DI BEI PERIODE 2020-2022 - Darno Darno; Longginus Gelatan (CV. Adiba Aisha Amira, 2025)
This study aims to determine the effect of financial leverage, profitability and earning per share on income smoothing with corporate governance as moderation in banking companies in the bei period 2020-2022. This study uses an associative method that aims to determine the effect or relationship between variables and uses documentation techniques in data collection. The analytical tool used to test the hypothesis is panel data regression analysis using Moderated Regression Analysis (MRA) with the results of the Common Effect Model (CEM) estimation with the help of the Evews 10 application. Partial analysis results show that financial leverage has no significant effect on income smoothing and profitability has a positive and significant effect on income sm oothing while earning per share has a negative and significant effect on income smoothing, corporate governance with audit committee proxy cannot moderate the relationship between financial leverage and earning per share on income sm oothing while corporate governance with audit committee proxy can moderate and strengthen the relationship between profitability and income smoothing.